Short-Term Calorie Restriction in Early Life Attenuates the Development of Proteinuria but Not Glucose Intolerance in Type 2 Diabetic OLETF Rats. (16th November 2011) - Nakano, Daisuke; Diah, Suwarni; Kitada, Kento; Hitomi, Hirofumi; Mori, Hirohito; Masaki, Tsutomu; Kobori, Hiroyuki; Nishiyama, Akira
Abstract : Childhood obesity is becoming more prevalent; however, the influence of obesity or dieting during childhood on outcomes in adulthood is poorly understood. The aim of this study was to examine the effects of short-term calorie restriction (CR) and high-calorie feeding with high-fat or high-sucrose diets during early life on the development of glucose tolerance and diabetic nephropathy in later life of Otsuka Long-Evans Tokushima fatty (OLETF) rats. Neither high-calorie intake nor CR at 7–13 weeks of age affected glucose tolerance of 27-week-old OLETF rats. On the other hand, proteinuria was lower at 27 weeks of age in CR rats than in the other rats. These results suggest that short-term CR at a young age protects against the development of renal injury in later life. In contrast, short-term high-calorie intake or CR at a young age does not appear to affect glucose metabolism in later life.